Incidence and Risk Factors for Short-Term Reoperations After Open First-Metatarsal Osteotomy for Hallux Valgus - Erjanti, Tuuli; Keskinen, Heli; Rissanen, Tiia; Mäkelä, Keijo; Lankinen, Petteri; Laaksonen, Inari; Koivu, Helka (SAGE Publications, 2026)
Background:
Despite the satisfactory results of hallux valgus surgery in general, the incidence of complications has been considerably high. This study evaluated the incidence and risk factors of short-term reoperations after surgical correction of hallux valgus deformity with first metatarsal osteotomy.
Methods:
We conducted a retrospective review of 685 consecutive open first-metatarsal osteotomies performed from 2013 to 2018 in a single university-hospital region. The number, indications, and type of reoperation were collected. The association between reoperation and patient’s age, sex, BMI, comorbidities, preoperative hallux valgus angle (HVA), hospital type, osteotomy type, and surgeon’s experience was analyzed.
Results:
There were 79 reoperations (11.5%) at a median of 14 months (range, 1-83) postoperatively. Fifteen reoperations were merely hardware removals. Most reoperations (46%) were performed because of residual deformity. Preoperative and postoperative HVA, diabetes, and type of osteotomy were statistically significant risk factors for all-cause reoperation both in univariate (P < .0001, P = .0052, and P < .0001, respectively) and multivariate analysis (P < .0001, P = .0059, and P < .0001, respectively). Overall, 4.9% of distal, 18.7% of midshaft, and 29.3% of proximal osteotomies were reoperated.
Conclusion:
The incidence of short-term (≤24-month) reoperations was higher than previously reported after open surgical correction of hallux valgus deformity with first metatarsal osteotomy. Larger preoperative and postoperative HVA, diabetes, and type of osteotomy were associated with revision surgery in this retrospective cohort. Proximal osteotomies had the highest risk for reoperation.